3363 Prognostic Value of Immune-Related Biomarkers in Resected Non-Small Cell Lung Cancer. (27th March 2019) - Veluswamy, Rajwanth R; Tuminello, Stephanie; Petralia, Francesca; Lieberman-Cribbin, Wil; Wang, Pei; Taioli, Emanuela
Abstract : OBJECTIVES/SPECIFIC AIMS: Immune cells within the tumor microenvironment (TME) play an important role in the development and progression of non-small cell lung cancer (NSCLC). However, data evaluating the impact of individual immune cell types on NSCLC outcomes is limited and often conflicting. We performed a meta-analysis of existing data and used The Cancer Genome Atlas (TCGA) to evaluate the effect of several immune cells on surgical outcomes of stage I-IIIA NSCLC. METHODS/STUDY POPULATION: PubMed was searched to identify eligible studies evaluating survival of surgically resected stage I-IIIA NSCLC patients according to immune cell infiltration. Meta-analysis was performed using a linear mixed-effects model to determine overall, disease specific and progression free survival. We then used a similar patient subset found in the TCGA to validate the meta-analysis findings. For the TCGA analysis, sample-specific scores for different immune cells were computed via xCell using level three RNAseq data. After stratifying the cohort by histologic subtype, the association between each cell type and survival was assessed via Cox Regression, while adjusting for stage, gender and smoking status. RESULTS/ANTICIPATED RESULTS: From the meta-analysis (37 articles eligible; N = 8, 162 patients), high levels of CD20+ B cells (hazard ratio [HR]: 0.36, 95% confidence interval [CI]: 0.15-0.85), natural killer (NK) cells (HR: 0.64, 95% CI: 0.41-1.0), and dendritic cells (0.34, 95% CI: 0.13-0.84) were significantly associated with better overall survival (OS); T regulatory cells (HR: 1.85, 95% CI: 1.35-2.54) were associated with worst OS. High CD8+ T cell infiltrates were associated with improved disease-free survival (DFS; HR: 0.85, 95% CI 0.73-0.99), while CD68+ macrophages (HR> 2.83, 95% CI: 1.28-6.24) were associated with worst DFS. In the TCGA cohort, lung adenocarcinomas rich in CD4 T cells, CD8 T cells, B cells, and NK cells were associated with improved OS in unadjusted analysis. In adjusted analysis, only NK cells were associated with improved OS (HR: 0.82, 95% CI: 0.69-0.98). There was no significant association of any immune cell type for DFS in lung adenocarcinomas and with both OS and DFS in Squamous Cell Lung Cancers (p>0.05 for all comparisons). DISCUSSION/SIGNIFICANCE OF IMPACT: The presence of tumor infiltration by specific immune cell subsets may potentially predict survival outcomes in resected stage I-III NSCLC patients. However, the impact of immune cells may not be similar in all histologic types and after adjusting for important clinical confounders.